Phylogenetic analysis and evolution of RNase P RNA in proteobacteria. - Brown, J W (1991)
The secondary structures of the eubacterial RNase P RNAs are being elucidated by a phylogenetic comparative approach. Sequences of genes encoding RNase P RNA from each of the recognized subgroups (alpha, beta, gamma, and delta) of the proteobacteria have now been determined. These sequences allow the refinement, to nearly the base pair level, of the phylogenetic model for RNase P RNA secondary structure. Evolutionary change among the RNase P RNAs was found to occur primarily in four discrete structural domains that are peripheral to a highly conserved core structure. The new sequences were used to examine critically the proposed similarity (C. Guerrier-Takada, N. Lumelsky, and S. Altman, Science 246:1578-1584, 1989) between a portion of RNase P RNA and the "exit site" of the 23S rRNA of Escherichia coli. Phylogenetic comparisons indicate that these sequences are not homologous and that any similarity in the structures is, at best, tenuous.